SARS-CoV-2 infection and exposure in cats and dogs in Romania - Cozma, Andreea Paula; Dascalu, Mihaela Anca; Buzdugan, Ioana; Tanase, Oana; Pavel, Geta; Enond, Christelle; Guillou, Noëlline; Peronnet, Juliane; Trinca, Lucia Carmen; Hristodorescu-Grigore, Smaranda; Marcelin, Anne-Geneviève; Calvez, Vincent; et al. (Frontiers in Veterinary Science, 2025)
SARS-CoV-2 has been described in more than 54 animal species, including wildlife, zoo animals and livestock. In the present study, conducted during 2021 and 2022 at the Faculty of Veterinary Medicine from Iasi, Romania, we studied the anthropogenic transmission of SARS-CoV-2 to pets by investigating active or prior infections of cats (n = 41) and dogs (n = 99) from the households of owners with confirmed COVID-19. Tests on an oropharyngeal swab from one cat revealed the presence of SARS-CoV-2 RNA 10 days after the onset of COVID-19 in its owner and another cat displayed SARS-CoV-2 seroconversion 15 days after the onset of COVID-19 in its owner but without the detection of SARS-CoV-2 viral RNA in its follow-up samples. Anti-N antibodies were detected in 7.2% (n = 7) of dogs and 12.5% (n = 5) of cats. All the seropositive cats were found to have SARS-CoV-2 neutralizing antibodies (NAbs) whereas only 42.9% (n = 3) of dogs displayed specific NAbs. These results are consistent with global reports, confirming the cross-species transmission of SARS-CoV-2. However, there is no evidence to suggest that companion animals are involved in the spread of SARS-CoV-2 to humans rather than simply being accidental hosts. Nevertheless, we describe several cases of potential anthropogenic infections during the pre-Omicron SARS-CoV-2 variant era.